Os direitos humanos de acessibilidade e locomoção das pessoas com necessidades especiais: a realidade paraense, com ênfase em Belém/PA - RAIOL, Raimundo Wilson Gama (Universidade Federal do Pará, 2015)
It presents the problematic daily faced by people with special necessities toward the archtecturing barriers in building destinied for public use and in collective transportation means, as well as toward the lack of accessible equipment and elements of the urban facilities. It makes use of survyed data about the people mentioned above. It analizes this problematic under the focus of human rights. It points out the indispensability of eliminating or adaptating the barriers mentioned above. It shows how the issue is dealt with by the international rules and how it is substantiated in national and state constitutional rules, in town organic laws and in infraconstituinal legislation specific in federal, provincial, and town levels, as well as in technical rules. It presents the precariousness of the physic-environmental structures, mainly in the town of Belém, State of Pará. It contains proposals for the maintenance of the accessibility and locomotion rules of the people involved and the concretion of these human rights.